Environmental Protection and Transitions From Conflict to Peace 2017
DOI: 10.1093/oso/9780198784630.003.0016
|View full text |Cite
|
Sign up to set email alerts
|

Victims of Environmental Harm During Conflict

Abstract: This chapter considers the interaction of some of the applicable norms related to liability and reparation for environmental damage in a post-conflict setting, including human rights and humanitarian law norms (including precedents) and their interaction with each other, with a focus on the potential consequences for victims. Using displacement as a specific case study, the discussion regarding potential consequences is supported by the learning that may be drawn from precedent reparations schemes, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…159 In contrast, proponents of the principle note that the more general nature of the principle is essential because in order 'to be effective it must be general in character but capable of devolving to the particular' . 160 In practice, the principle has demonstrated this capacity through its application to both specific areas of IEL, such as ozone depletion, as well as to more general concepts, as in the case of environmental protection and development.161 Furthermore, they note that it is 'characteristic of general principles with a wide scope of application [ . .…”
Section: The Legal Status Of the Precautionary Principlementioning
confidence: 99%
See 4 more Smart Citations
“…159 In contrast, proponents of the principle note that the more general nature of the principle is essential because in order 'to be effective it must be general in character but capable of devolving to the particular' . 160 In practice, the principle has demonstrated this capacity through its application to both specific areas of IEL, such as ozone depletion, as well as to more general concepts, as in the case of environmental protection and development.161 Furthermore, they note that it is 'characteristic of general principles with a wide scope of application [ . .…”
Section: The Legal Status Of the Precautionary Principlementioning
confidence: 99%
“…In Rwanda and Mali, as McCoy explains, 'horizontal inequalities' were major causal factors of conflict, particularly group inequalities in land ownership and access to resources.157 Using transitional justice mechanisms, the Truth Commission in Kenya, for example, found that 'historical grievances over land' constituted the 'single most important driver of conflicts and ethnic tension in Kenya' ,158 while 'close to 50 percent of statements and memorandum received by the Commission related to or touched on claims over land' .159 UN Secretary-General Kofi Annan has also recognized transboundary water resources, food insecurity, land concentration, and access to landbased resources as root causes of conflict, which are often coupled with poverty and social inequality, particularly, he says, in African and Latin American countries. 160 And, of course, due to future climate change impacts on natural resources it is likely that we will see greater land inequalities, water disputes, food insecurity, and resourcedependent livelihoods lost across the globe and so the resource-competition/ conflict nexus is only going to increase in importance.…”
Section: Poverty and Historical Inequalitiesmentioning
confidence: 99%
See 3 more Smart Citations